The first cat in space ate pizza - Barnett, Mac; Harris, Shawn (Artist) (New York, NY : Katherine Tegen Books, 2022)
Something terrible is happening in the skies! Rats are eating the MOON! There's only ONE hero for the job, a bold and fearsome beast bioengineered in a secret lab to be the moon's savior and Earth's last hope! And that hero is--a cat. A cat who will be blasted into space! Accompanied by the imperious Moon Queen and LOZ 4000, a toenail clipping robot, the First Cat in Space journeys across a fantastic lunar landscape in a quest to save the world. Will these unlikely heroes save the moon in time? And will the First Cat in Space ever eat some pizza?
School Library Journal starred, May 2022
Pub Weekly, April 2022
Bulletin (Center for Children's Books), April 2022
2.8
3-6
Keywords: Cats -- Comic books, strips, etc -- Juvenile fiction; Robots -- Comic books, strips, etc -- Juvenile fiction; Space flight -- Comic books, strips, etc -- Juvenile fiction; Rats -- Comic books, strips, etc -- Juvenile fiction; Moon -- Comic books, strips, etc -- Juvenile fiction; Adventure stories; Humorous stories; Cats -- Fiction; Robots -- Fiction; Space flight -- Fiction; Rats -- Fiction; Moon -- Fiction; Pizza -- Fiction; Adventure and adventurers -- Fiction; Humorous comics; Action and adventure comics; Graphic novels; Comics (Graphic works)